2020
DOI: 10.3389/fphar.2020.590972
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Exosomes in Pulmonary Fibrosis

Abstract: Pulmonary fibrosis is closely associated with the recruitment of fibroblasts from capillary vessels with damaged endothelial cells, the epithelial mesenchymal transition (EMT) of type II alveolar epithelial cells, and the transformation of fibroblasts to myofibroblasts. Recent studies suggest that EMT is a key factor in the pathogenesis of pulmonary fibrosis, as the disruption of EMT-related effector molecules can inhibit the occurrence and development of PF. With the numerous advancements made in molecular bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 137 publications
(172 reference statements)
0
16
0
Order By: Relevance
“…Owing to the promising therapeutic potentials of stem cells-derived exosomes, extensive attention has been drawn to focus on their functions [ 28 ]. Recently, the exosomes secreted from BMSCs have been identified to exhibit various ameliorative roles against diverse types of diseased cells in human [ 29 , 30 ]. To increase our understandings of BMSCs-derived exosomes-related therapies, exploring the underlying molecular mechanisms are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the promising therapeutic potentials of stem cells-derived exosomes, extensive attention has been drawn to focus on their functions [ 28 ]. Recently, the exosomes secreted from BMSCs have been identified to exhibit various ameliorative roles against diverse types of diseased cells in human [ 29 , 30 ]. To increase our understandings of BMSCs-derived exosomes-related therapies, exploring the underlying molecular mechanisms are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies also found that ADSCs transplantation can improve the repair of endometrial injury ( Shao et al, 2019 ). Exosomes are nanoscale vesicles, approximately 30–100 nm in diameter, released into the extracellular environment in the form of exocytosis after fusion of intracellular Multivesicular Bodies (MVBs) with the cell membrane ( Xie and Zeng, 2020 ). Compared with other vectors, exosomes may be a promising therapeutic strategy due to their lower immunogenicity, non-cytotoxicity, and non-mutagenicity to receptors.…”
Section: Discussionmentioning
confidence: 99%
“…They convey proteins, lipids, miRNAs, long non-coding RNAs, DNA, enzymes and other factors responsible of cell-to-cell communication, epigenetic modifications. Composition of exosomes is influenced by microenvironment and determines the maintenance or the rupture of cellular homeostasis (173,174).…”
Section: Epigeneticsmentioning
confidence: 99%